The training program in basic gymnastics jumps at the stage of initial training - Oksana Zaplatynska (Kharkiv State Academy of Physical Culture, 2015)
Purpose: improving of the technical training of girls that are engaged in rhythmic gymnastics at the stage of initial training. Materials and Methods: for the development of a training program for jumping in athletes who are engaged in rhythmic gymnastics at the stage of initial training conducted analysis of scientific literature. Results: it was determined that the absorption of the rhythmic structure of elements greatly accelerates and facilitates the process of studying in a cyclic (athletics) and acyclic sports (judo, wrestling). This is a prerequisite for the development of the training program of the jumps through assimilation rates their performance. These various methods of influence on the development of sense of rhythmic gymnasts at the stage of initial preparation and learning the rhythmic structure of the basic jumps. Conclusions: the program of teaching basic jumping for gymnasts at the stage of initial training, a variety of methods of influence on the development of sense of rhythm and learning the rhythmic structure of the elements was developed. The project of the training session for the development of a sense of rhythm and learning the rhythmic structure of the basic jumps was developed.